Estudio y diseño de la pavimentación y drenaje pluvial, de las calles de la ciudadela Jardines de conchales, del cantón Santa Rosa, provincia de el Oro.Estudio y diseño de la pavimentación y drenaje pluvial, de las calles de la ciudadela Jardines de conchales, del cantón Santa Rosa, provincia de el Oro. - Pineda Torres, Arelis Patricia (2015)
The lack of study and design of the paving and rainwater drainage from the streets of the Garden Citadel Conchales belonging to Santa Rosa Canton, hampers vehicular and pedestrian traffic in its entirety, because their streets contain a layer of tread granular material and in the rainy season water puddles arise due to lack of drainage system rainwater. Arises aim develop the study and design of the paving and storm drainage, streets of the Citadel, for social and economic progress of their inhabitants. Research and inquiry that was conducted using the method of literature review, consultations on the web, field research and surveying work in direct contact with the sector. The results of topography, soil studies, analysis of the asphalt mix, design standards, used to design the structure of the pavement, the drainage system and environmental impact study. The design is for a road Order IV, designed with a design speed of 60 km / h. The pavement structure has a thickness of 5 cm asphalt base 15 cm Class II, Class II sub-base of 20 cm and subgrade improvement of 30 cm.